The Application of Freeze Clauses in Esports Contracts Based on Balances Principle - Herlianto, Fahrian; Wahyuni, Ridha (Al-Risalah, 2025)
The rapid growth of the esports industry in Indonesia has led to increasingly structured employment contracts between players and teams. Among the most contentious provisions is the freeze clause, which grants teams the authority to suspend players' professional activities without clear justification, time limits, or compensation. This study aims to examine the legality of such clauses within the framework of Indonesian contract law, focusing on the principle of balance and the protection of parties in unequal bargaining positions. Employing a normative juridical methodology, this research uses statutory analysis and case-based interpretation to evaluate the enforceability of freeze clauses. The findings reveal that when applied unilaterally, freeze clauses violate the principle of good faith and may constitute misbruik van omstandigheden (abuse of circumstances). Such clauses not only disrupt the professional careers of esports players but also undermine the foundational values of fairness and reciprocity in contract law. The originality of this research lies in its legal scrutiny of esports contract practices, a relatively underexplored area in Indonesian legal scholarship. The study highlights the urgent need for contract reforms and the development of protective legal standards within the esports industry. It also offers practical pathways for dispute resolution—through mediation, arbitration, or litigation—providing strategic guidance for players seeking justice.